Comparison of Debulking Combined with Intralesional Triamcinolone Acetonide Injection Versus Debulking Alone, for the Treatment of Earlobe and Helical Keloids. - Radhi, Yasir T.; Al-Hamamy, Hayder (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Keloids of the ear present a significant clinical challenge, with surgical excision alone associated with high recurrence rates (45%–100%). Various adjuvant treatments have been explored to improve outcomes, with intra-lesional corticosteroids showing promise.Objectives: To evaluate the effectiveness and safety of debulking combined with intralesional injection of triamcinolone acetonide versus debulking alone in treating earlobe and helical keloids.Methods: This study was conducted at the Department of Dermatology and Venereology, Baghdad Teaching Hospital, from January 2014 to October 2015. Twenty-eight female patients with 67 keloid lesions resulting from ear piercing were enrolled and randomly divided into two groups. Group 1 underwent debulking followed by intralesional injection of triamcinolone acetonide (0.25 mg to 1 mg), while Group 2 received debulking alone. The treatment response was assessed over six months using keloid height measurements, a visual analogue scale (VAS) for improvement, patient satisfaction scores, and recurrence rates.Results: Group 1 demonstrated more significant improvement, with a mean VAS score of 8.8 ± 2.00 compared to 3.5 ± 2.63 in Group 2. Patient satisfaction was also higher in Group 1 (8.6 ± 2.38) than in Group 2 (3.5 ± 2.40). The recurrence rate was markedly lower in Group 1 (13.3%) compared to Group 2 (92.3%). No significant side effects or systemic adverse effects were observed in either group.Conclusion: Debulking combined with intralesional triamcinolone acetonide injection is a more effective treatment for earlobe and helical keloids than debulking alone. This approach is simple, cost-effective, and well-tolerated, leading to higher patient satisfaction and significantly lower recurrence rates.